Chronic recurrent multifocal osteomyelitis in association with pyoderma gangraenosum. Issue 1 (December 2016) - Wurm, Matthias; Brecht, Ines; Lell, Michael; Brunner, Kathrin; Mitsimponas, Konstantinos; Chada, Martin; Jahn, Julia; Neukam, Friedrich-Wilhelm; von Wilmowsky, Cornelius
Abstract Background Chronic recurrent multifocal osteomyelitis (CRMO) is a rare acquired inflammatory skeletal disorder of unknown origin. CRMO was first described by Gideon in 1972 and mainly affects children and young adults of female gender. The CRMO is part of the clinical picture of non-bacterial Osteomyelitis (NBO) and typically presents a relapsing recurring course with both remission and spontaneous exacerbation. CRMO is typically encountered in the limbs and the metaphysis of long bones in particular. Usually the clinical symptoms include painful swellings of the affected regions. This case report describes the rare case of a CRMO of the mandible in association with pyoderma gangraenosum. Case presentation A 14-year old female caucasian patient, residing in the south of Germany, presented in the oncological outpatient clinic of our Department of Paediatrics and Adolescent Medicine in June 2014 complaining of increasing neck pain and progressive swelling at her left cheek ongoing for about 6 weeks. These symptoms had been occurring quarterly for 4 years, but had never been as pronounced. Blood biochemistry showed a moderately elevated CRP (35 mg/l) and a significantly increased blood sedimentation rate (BSR 48/120 mm). The panoramic radiograph, however, revealed a bone alteration in the left mandibular region. Further investigations confirmed the diagnosis of CRMO. Conclusion The present case underlines the fact that rare diseases might occasionally present with even more rare symptoms. These occasions can obviously be considered to present a considerable diagnostic challenge.